Corporate/Non-profit Organisations Partnerships in France: A Critical Examination of the Motivational Factors leading to Corporate-NGO Partnerships - Peruzzo, Cristiana (2008)
In the last decade, the trend of Non-Governmental Organisations (NGOs) working in cooperation with business has increased substantially. Leaders of the non-profit sectors as well as business leaders have recognised the importance of adopting a collaborative approach to tackle some of the global challenges that society is facing more efficiently. This dissertation discusses the phenomenon of Corporate-NGOs partnerships by looking at the motivational drivers that push both partners to engage in more collaborative efforts. In the first chapter the main aspects of Corporate-NGOs partnerships are introduced in order to situate the emergence of such trend within the historical context of relations across the two sectors. In addition, the author will explore the forces that allow the partnership trend to develop dramatically in the past years both internationally and within the national context of France. Chapter II will provide the necessary theoretical ground upon which the empirical evidence can be based by focusing in particular on the frameworks provided by Selsky and Parker (2005). Chapter III will describe the research methodology utilised to analyse the CARE-Lafarge case study presented in the empirical chapters. Having addressed and discussed the research question of finding the motives behind corporate/NGO partnership in chapters IV and V, the final chapter will discuss the main implications of the author's research in order to generate recommendations.